A two-tier approach to the optimization of a biomass supply chain for pyrolysis processes. (January 2016) - Paolucci, Nicoletta; Bezzo, Fabrizio; Tugnoli, Alessandro
Abstract: The optimal supply chain configuration for biomass production on a given territory is identified by a two-tier approach, which considers both the environmental and the economic points of view. The first tier performs a quick evaluation of the supply chain, based on simplified assumptions and on average values of the parameters characterizing the geographical territory. The second tier allows for the inclusion of spatially explicit parameters of the territory and realizes a more detailed optimization of the supply chain using a multi-objective Mixed Integer Linear Programming framework. A demonstrative case study is presented for the bio-fuel supply to a centralized electric power plant. The considered supply chain is based on miscanthus, cultivated in marginal terrains and converted to pyro-oil in a number of delocalized plants for long distance shipment. The results obtained from the two tiers of the model provide quantitative information, to support quick and effective decision making on the optimal configuration of the supply chain in terms of plant size, location, transport logistics and cultivation. Highlights: A two-tier approach was proposed for the optimal design of biomass supply chains. Both the environmental (greenhouse gases) and the economic aspects were evaluated. The first tier provided a quick screening of the supply chain. The second tier generated optimal configurations, accounting for the territorial features. A demonstrative case study was presented for the bio-fuel from pyrolysis of miscanthus.